The Impact of COVID-19 Infection for Breastmilk Production in Lactating Women - Xia Huang; Jiatian Ye; Xiaorong Qi (IMR Press, 2024)
Background: Since the global outbreak of coronavirus disease 2019 (COVID-19), its rapid spread has had a dramatic impact on the physical/mental health of people of all ages, including lactating women. We chose to study whether COVID-19 affected breastfeeding of in China. Since there has been no relevant research on this topic in China our team planned to study this topic. Methods: The study population was drawn from the postpartum clinic of the Fourth People's Hospital of Zigong City, Sichuan province, China, from 07/12/2022 to 01/04/2023. This group comprised lactating women who manually expressed their milk due to various reasons, rather than directly nursing their infants. The population was classified into two groups: the infected group and uninfected group, based on their current COVID-19 status. COVID-19 infection was defined as a positive result in either the COVID-19 nucleic acid test (reverse transcription-polymerase chain reaction/polymerase chain reaction (RT-PCR/PCR)) or the COVID-19 antigen test. We retrospectively assessed their breast milk production and infant growth and development over a subsequent 4-month period. Results: The study encompassed a total of 79 lactating women, comprising 45 in the infected group and 34 in the uninfected group. There was a statistically significant difference in the rate of breast milk production between the COVID-19 infected and uninfected groups (χ2 = 6.067, p < 0.05). Logistic regression analysis revealed an elevated risk of reduced breast milk production in the COVID-19 infected group compared to the uninfected group (odds ratio (OR) 3.163, 95% confidence interval (CI): 1.248-8.017). After adjusting for confounding factors, the result remained consistent (OR 3.339, 95% CI: 1.134-9.833). Regarding the growth and developmental status of their infants, over the course of a 4-month follow-up period, breast milk production showed no significant adverse effects on their growth and development. Conclusions: Our retrospective study illustrated that COVID-19 infection can result in reduced breast milk production. In the short term, breast milk from infected mothers does not impact the height and weight gain of their infants, thus advocating for infected mothers to continue breastfeeding.